Transcriptome profiling of Toona ciliata young stems in response to Hypsipyla robusta Moore - Song, Huiyun; Li, Yue; Wang, Zhi; Duan, Zhihao; Wang, Yueyang; Yang, Endian; Que, Qingmin; Chen, Xiaoyang; Li, Pei (Frontiers in Plant Science, 2022)
Toona ciliata is a traditional woody plant that can be used as a medicinal material in China. The extracts of its roots, stems, leaves, and flowers all have a wide range of bioactive compounds. However, T. ciliata has been facing an unresolved pest problem caused by Hypsipyla robusta Moore (HRM), which seriously affects its growth and development. In this study, the expression level of TcMYB3 gene reached the maximum (28-fold) at 12 h and transcriptome sequencing of young stems eaten by HRM for 0, 3, 12, and 21h were performed. A large number of differentially expressed genes (DEGs) were identified including jointly up-regulated genes (263) and down-regulated genes (378). JA synthesis and signaling transduction, terpene biosynthesis, and MAPKs signaling pathway were analyzed in depth and found that TcOPR3, TcJAR1, TcJAZs, and TcTPS9 genes possessed anti-insect potential. Moreover, MYBs and ERFs transcription factors (TFs) family were significantly strengthened that may participate in induced defense mechanism in T. ciliata. These data not only provide insights into the molecular mechanisms in resistance of T. ciliata to HRM but also helps to explore the new biocontrol strategies against insects in eco-friendly woody plant.